2003
DOI: 10.1021/ic0342853
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Polyol Synthesis of CuInTe2 and CuInSe2 Nanoparticles

Abstract: Nanoparticles of the CuInTe(2) (CIT) and CuInSe(2) (CIS) alloys have been prepared using the microwave-assisted polyol method. In this simple and quick reaction the polyol is both the solvent and the reducing agent. XRD studies show that nanoparticles of CIT and CIS are formed in the body-centered tetragonal structure and their average diameters are approximately 94 and approximately 83 nm, respectively. Electron microscopy studies show that these formed particles are poorly aggregated with a mean diameter of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(68 citation statements)
references
References 43 publications
1
67
0
Order By: Relevance
“…Some studies have shown that the synthesis of nanoparticles with the technique is generally quite fast, simple, and energy efficient compared with conventional hydrothermal synthesis. [17,18] To the best of our knowledge, there are no reports on the preparation of highly stable and uniformly sized colloidal carbon nanospheres by the technique.…”
Section: Preparation and Characterization Of The Aunp/c Hybrid Materialsmentioning
confidence: 99%
“…Some studies have shown that the synthesis of nanoparticles with the technique is generally quite fast, simple, and energy efficient compared with conventional hydrothermal synthesis. [17,18] To the best of our knowledge, there are no reports on the preparation of highly stable and uniformly sized colloidal carbon nanospheres by the technique.…”
Section: Preparation and Characterization Of The Aunp/c Hybrid Materialsmentioning
confidence: 99%
“…In previous work, we proposed a mechanism for the formation of CuInSe 2 (CIS) and CuInTe 2 (CIT) nanoparticles. [14] The proposed mechanism was based on the fact that the reduced metallic particles react with a second metallic element and with the chalcogenide under microwave irradiation in order to form a ternary chalcogenide compound. For the abovementioned compounds, CIS and CIT, the additional metallic element was indium.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…The use of domestic multimode microwave (Gabriel et al 1998;Grisaru et al 2003;Harpeness and Gedanken 2004) or single-mode microwave ovens (Kadirvelu et al 2000;Katsuki and Komarneni 2003) for the fabrication of inorganic nanomaterials is becoming a common technique. The main advantage of this method when compared to other synthetic nanoparticle techniques is the short reaction time.…”
Section: Introductionmentioning
confidence: 99%